Organizational Excellence And Its Role In Achieving The Competitive Advantage Of Abu Dhabi University: Applied Study To The Faculties Of Abu Dhabi University - Sultan Saif Ali Al Darmaki; Khairunneezam Mohd Noor (Usuli Faqih Research Centre PLT, 2024)
Vol 12 No 1 (2021): Perdana: December Issue